Mechanical analogy of statement networks - Cholewa, Wojciech (Zielona Góra: Uniwersytet Zielonogórski)
The paper demonstrates briefly the reasoning capabilities in condition monitoring offered by systems based on statement networks. The usefulness of the networks considered results among others from possibilities of their optimization related to the minimization of contradictions between rules acquired from different knowledge sources. A mechanical analogy of such networks introduces an interpretation of statements as material points that are able to move.
Keywords: statement network; dynamic statement; contradictory rules; belief network